Illegal and Unauthorized Medical Treatment In Therapeutic Transactions - Adianie, Nadya; Djajaputra, Gunawan (UNES Law Review, 2024)
In this era and age, doctors and patients are mostly bound by transactional relationship which generally written down under a therapeutic contract. The contract acts as mutual agreement between both the practitioner and patient that ensures the medical procedure will be performed professionally and highlights responsibilities of the practitioner towards patient. It becomes problematic when medical professionals performs beyond their responsibilities of what has been written under the contract which would cause of what should have been a legal procedure to become an unlawful act. Most common people wouldn’t understand and comprehend what is actually written under the contract so it becomes difficult to determine whether the medical procedure is legal or not.